Scirrotherium Antelucanus, a new species of Pampatheriidae (Mammalia, Xenarthra, Cingulata) from the Upper Miocene of Costa Rica, Central America - Laurito, César A. (2011)
For the first time the genus Scirrotherium is recorded and a new species is described for the early Hem- phillian of Costa Rica. This finding constitutes a new clue about the early arrived of South American heralds to Central American during Pre-Great American Biotic Interchange, increasing by at least 3 Ma the record of the Pampatheriidae family in the Northern Hemisphere. The new Central America species described herein differs from the South American species of Scirrotherium because they have osteoderms with an inconspicuous ornamentation, a plain central figure and a remarkable area size.Keywords: Mammalia, Xenarthra, Pampatheriidae, Scirrotherium, Upper Miocene, Costa Rica, pre-GABI.